PENGARUH ASAM OLEAT, PROPILEN GLIKOL DAN ISOPROPIL ALKOHOL PADA FORMULA PATCH TRANSDERMAL KALIUM LOSARTAN DENGAN MATRIKS HIDROKSIPROPIL METILSELULOSA DAN ETIL SELULOSA - , OKTAVIA INDRATI, Dr. Akhmad Nugroho, M.Si, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
There are many factors that affect the physicochemical properties of the transdermal patch. This study aimed to assess the effects of oleic acid, propylene glycol and isopropyl alcohol on potassium losartan transdermal patch formulas with ethyl cellulose and hydroxypropyl methylcelullose as matrix. In addition, this study also wanted to know whether the prediction of the plasma concentrations of the losartan on a transdermal patch could reach or not the therapeutic concentration level in human. Proportions of oleic acid, propylene glycol and isopropyl alcohol on transdermal patches were determined by using software program of Design Expert 7. Transdermal patches were made by using moulding method and their physicochemical properties including the visual impression, weight, thickness, loss on drying, the moisture uptake, the drug content and folding endurance were evaluated. The best formula was determined based on its appropriate physicochemical properties. The in vitro permeation study of the patch was conducted by using a vertical type diffusion cell and the data obtained were analyzed by using software program of WinSAAM 3.0.7. The results showed that increasing the amount of oleic acid was proportional to the increasing of thickness, weight and drug content of the patch but inversely proportional to the increasing of loss on drying and moisture uptake. Increasing the amount of propylene glycol was also proportional to the increasing of thickness, weight, loss on drying and drug content but inversely proportional to the increasing of moisture uptake. Meanwhile, increasing the amount of isopropyl alcohol was proportional to the increasing of weight, moisture uptake and drug content but inversely proportional to the increasing of thickness and loss on drying. The best formula obtained consisted of 5.3% v/v oleic acid, 1.0% v/v propylene glycol and 7.8% v/v isopropyl alcohol. In addition, the predicted in vivo plasma concentration of the losartan transdermal patch was still far below the plasma concentration of oral delivery in human with the single dose of 40 mg.